None of Your Business World Data Flows, Electronic Commerce, and the European Privacy Directive. - Swire, Peter P. (Brookings Institution Press, 2010)
The historic European Union Directive on Data Protection will take effect in October 1998. A key provision will prohibit transfer of personal information from Europe to other countries if they lack ""adequate"" protection of privacy. If enforced as written, the Directive could create enormous obstacles to commerce between Europe and other countries, such as the United States, that do not have comprehensive privacy statutes. In this book, Peter Swire and Robert Litan provide the first detailed analysis of the sector-by-sector effects of the Directive. They examine such topics as the text of the.